O dano existencial nas relações de emprego e o meio ambiente de trabalho não hígido - Passos, Fábio Silva Ferraz dos (2018)
This dissertation has as main objective the approach of the existential damage in the labor relations and its consequences for the worker because it is a very serious injury that reaches the worker in his projects of life and relations. The study begins with research related to human and fundamental rights, bringing the historical evolution, going through the main events and knowing the different suits, until we get to the present day. Next, the important concepts are identified to follow the appreciation of the theme, including human dignity, decent work, healthy working environment, employer leadership, as well as brief lines on civil liability and damage to their species. Environmental health and safety conditions will be addressed in order to demonstrate that time management is important for the efficiency of production but also for the worker who suffers from the employer's abuses and disregard of standards. the journey and the rest periods the main ground for the claims of existential damages found in the jurisprudence. Finally, the concept of existential damage was identified as the key theme of this research, revealing its roots, characteristics and effects when brought to the field of work, its arrival in Brazil and the expectations on this subject after Law no. 13.467/2007, which instituted the so-called labor reform and will also receive comments, especially regarding the insertion of this new autonomous modality of damage and its effects.